Receptor material containing cyclohexyl side chain as well as preparation method and application thereof
By introducing cyclohexyl-linear chain composite side chains into non-fullerene small molecule acceptor materials to regulate intermolecular interactions, the problem of improving the photoelectric characteristics and efficiency of existing materials in organic solar cells is solved, and more efficient charge transfer and photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202411679531.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There is still room for improvement in the photoelectric properties and efficiency of existing non-fullerene small molecule acceptor materials in organic solar cells, especially in terms of intermolecular interactions and blended film morphology.
The cyclohexyl-linear chain composite side chain design with large volume cyclohexyl as a sterically hindered structure is designed to enhance the polarization rate of molecules and the overlap of electron orbits by regulating intramolecular and intermolecular interactions, promote charge transfer and reduce energy loss.
This design significantly improves the efficiency of organic solar cells, enhances the polarization rate and charge transport characteristics of molecules, and improves the morphology and photophysical properties of the blended film.
Smart Images

Figure CN119504795A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic photoelectric materials, in particular to an acceptor material containing a cyclohexyl side chain and a preparation method and application thereof. Background Art
[0002] In recent years, organic solar cells have experienced rapid development, achieving continuous breakthroughs in energy conversion efficiency. This development is largely due to the development of non-fullerene small molecule acceptors. These acceptors have narrow band gaps and exceptionally high absorption coefficients, forming complementary absorption and energy-level matching with most broadband donors. Non-fullerene acceptors typically have an ADA-type fused ring structure. The electron-donating D unit and the end-capping acceptor A unit modulate the absorption range and band gap through intramolecular electron push-pull effects. The rigid fused ring structure extends conjugation, improves molecular planarity, and promotes π-electron delocalization. π-π stacking between the terminal A units provides the primary charge transfer pathway for molecular arrangement. In addition to regulating the A and D units, side chain modification is also crucial in the common design methods for ADA-type small molecule synthesis. Side chain modifications, including topology (linear or branched), branch points, symmetry breaking, and size, are the most commonly used methods for precisely regulating molecular solubility, crystallization, and packing behavior.
[0003] Here, we propose a strategy to construct a novel non-fullerene small molecule receptor material with a cyclohexyl-linear chain composite side chain. The introduction of bulky cyclohexyl groups as steric hindrance structures in the side chains of small molecule receptors can affect the molecular planarity, molecular arrangement, and optoelectronic properties by regulating intramolecular and intermolecular interactions. The steric hindrance effect generated by the combination of flexible alkyl units and rigid cycloalkyl units can optimize the crystallization and interaction between molecules, and further improve the morphology and photophysical properties of the blend film. The optimal intramolecular and intermolecular interactions induced by steric hindrance can enhance the polarizability of the molecule, promote the overlap of intermolecular electronic orbitals, and promote the delocalization of the charge transfer pathway, thereby reducing energy loss and improving efficiency. The "cycloalkyl-linear" composite side chain engineering is a potential new side chain that can finely control the properties of materials. Summary of the Invention
[0004] The purpose of this application is to provide an acceptor material containing a cyclohexyl side chain, a preparation method and application thereof, and to open up a new path for the synthesis of new organic semiconductor materials.
[0005] The present invention provides an acceptor material containing a cyclohexyl side chain, the structural formula of which is one of Y-C1 and Y-C2, as shown below:
[0006]
[0007] The preparation method of the receptor material containing cyclohexyl side chains comprises the following steps:
[0008] Step 1: Using trans-p-pentylcyclohexylcarboxylic acid as the raw material, first react with tribromothiophene through a Friedel-Crafts acylation reaction, and then carry out a cyclohydrolysis reaction with ethyl mercaptoacetate to obtain 3-alkyl-thieno[3,2-b]thiophene-2-carboxylic acid; then carry out a high-temperature decarboxylation reaction under the catalysis of copper powder to obtain compound A;
[0009] Step 2: Compound B is obtained by Stille coupling reaction catalyzed by Pd(PPh3)2Cl2;
[0010] Step 3: Compound B undergoes intramolecular Cadogan cyclization reaction with triethyl phosphite, and then undergoes alkylation reaction with 2-ethylhexyl as a side chain to obtain compound C;
[0011] Step 4: Compound C is subjected to Vilsmeier Haack reaction to prepare dialdehyde compound D;
[0012] Step 5: Compound D and terminal unit IC-2F are subjected to Knoevenagel polycondensation reaction to obtain compound E, ie, an acceptor material containing a cyclohexyl side chain.
[0013] Furthermore, the specific operation of step 1 is as follows: at 0°C, oxalyl chloride is added to a dichloromethane solution of the compound trans-p-pentylcyclohexylcarboxylic acid, stirred at room temperature for 5 hours, and after removing the solvent and the remaining oxalyl chloride, a colorless acid chloride is obtained; then, anhydrous AlCl3 is added in batches to a stirred solution of halogenated thiophene and the prepared acid chloride, and the resulting solution is stirred at room temperature for 4 hours, and then cold water is slowly added to quench the reaction, and the organic phase is extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent is removed under reduced pressure to obtain an orange oily liquid, which is mixed with K2CO3 in DMF solvent, and ethyl mercaptoacetate is added dropwise at 60°C in a nitrogen atmosphere, stirred overnight, and then poured into water, and the organic phase is extracted with dichloromethane, dried over anhydrous Na2SO4, and NaOH is added after removing the solvent under reduced pressure. After the mixture is refluxed in an ethanol solvent overnight, cooled to room temperature, the liquid is acidified with concentrated hydrochloric acid, and a yellow solid is collected by filtration. The solid was washed with water to remove excess hydrochloric acid, and then washed with petroleum ether to obtain a light pink solid. The mixture was heated in a sand bath at 260° C. with copper powder in a quinoline solvent, stirred and refluxed for 3 h, and the mixture was cooled to room temperature. n-hexane was added to the mixture, and the mixture was washed with hydrochloric acid. The organic phase was extracted with petroleum ether, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. The compound A was purified by silica gel chromatography to obtain a colorless oily liquid. In the above operation, the molar ratio of trans-p-pentylcyclohexylcarboxylic acid and the oxalyl chloride is (1-1.2):3, preferably 1:3; the molar ratio of the 3-bromothiophene and the acyl chloride is 1:1; the molar ratio of the 3-bromothiophene and anhydrous AlCl3 is 1:1; the molar ratio of the 3-bromothiophene and K2CO3 is 1:2; the molar ratio of the 3-bromothiophene and ethyl mercaptoacetate is 1:1; and the molar ratio of the 3-bromothiophene and NaOH is 1:2.
[0014] Furthermore, the step 2 is specifically as follows: under a nitrogen atmosphere, anhydrous tetrahydrofuran is used as a solvent, compound A is used as a raw material, 2.4M n-butyl lithium is added dropwise at -78°C, stirred at -78°C for 1 hour, tributyltin chloride is added, and then the temperature is gradually raised to room temperature and stirred overnight. After the reaction is completed, deionized water is added to quench, the organic phase is extracted with petroleum ether, dried over anhydrous Na2SO4, and the solvent is removed under reduced pressure. Anhydrous toluene solution is added, followed by addition of 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole and catalyst Pd(PPh3)Cl2, stirred and refluxed for 12 hours. After the reaction is completed, it is cooled to room temperature, the solvent is removed under reduced pressure, and purified by silica gel chromatography to obtain a red solid compound B; the molar ratio of compound A to n-butyllithium in the above operation is 1:1; the molar ratio of compound A to tributyltin chloride is 1:1. The molar ratio of the compound A to 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole is 3:1.
[0015] Furthermore, the step 3 is specifically as follows: under a nitrogen atmosphere, a mixed solvent of triethyl phosphite and o-dichlorobenzene of compound B is heated to 180°C for overnight reaction. After the reaction, the solvent is distilled off under reduced pressure to obtain a yellow solid for the next step, 1-bromo-2-ethylhexane, potassium carbonate, potassium iodide and DMF are added to the obtained yellow solid, and the mixture is reacted at 80°C for 12 hours under a nitrogen atmosphere. After the reaction is completed, water is added to quench the mixture, the mixture is washed with saturated brine and the organic phase is extracted with dichloromethane, dried over anhydrous Na2SO4, the solvent is removed under reduced pressure, and purified by silica gel chromatography to obtain an orange solid compound C; in the above operation, the molar ratio of compound B to 1-bromo-2-ethylhexane is 1:10; the molar ratio of compound B to potassium carbonate is 1:10; and the molar ratio of compound B to potassium iodide is 3:1.
[0016] Furthermore, the step 4 is specifically as follows: under a nitrogen atmosphere, adding phosphorus oxychloride to anhydrous DMF at 0°C, reacting for 0.5h, then adding a 1,2-dichloroethane solution of compound C to the mixed system, reflux at 80°C overnight, quenching with a saturated aqueous sodium carbonate solution, and stirring for 1h to fully hydrolyze the product, then extracting the organic phase with dichloromethane, drying with anhydrous Na2SO4, removing the solvent under reduced pressure, and purifying with a silica gel chromatography column to obtain an orange solid compound D; wherein the molar ratio of compound C to phosphorus oxychloride is 1:3.
[0017] Furthermore, the step 5 is specifically as follows: adding the terminal group 5,6-difluoro-3-(dicyanomethyl)indone to compound D, adding anhydrous chloroform and pyridine to the mixed system under a nitrogen atmosphere, stirring and reflux for 12 hours, and after the reaction, pouring the mixed system into methanol to dissolve excess terminal reactants, filtering the precipitate and purifying it with a silica gel chromatography column to obtain a black purple solid compound E; wherein the ratio of compound D to 5,6-difluoro-3-(dicyanomethyl)indone is 1:7.
[0018] Application of the acceptor material containing cyclohexyl side chains in the preparation of organic solar cell devices.
[0019] Furthermore, the donor material selected in the preparation of the organic solar cell device is PM6; the mass ratio of the PM6 to the small molecule acceptor material containing cyclohexyl side chains is 1:1.2.
[0020] The beneficial effects of the present invention are as follows: (1) Based on the traditional ADA structure with the Y series analogue as the core, the present invention introduces a bulky sterically hindered side chain, designs different small molecule receptor materials, and introduces a bulky cyclohexyl group in the side chain to increase the steric effect. This unique design regulates intramolecular and intermolecular interactions, enhances the polarizability of the molecule, promotes the overlap of intermolecular electron orbitals, promotes the delocalization of the charge transfer pathway, thereby reducing energy loss and improving efficiency. The reaction conditions are simple and the purification is easy, which has good practical application prospects.
[0021] (2) The present invention can broaden the absorption of molecules, increase the absorption coefficient of molecules, and reduce the HOMO energy level of small molecule materials by introducing IT-2F as the terminal group. By introducing cyclohexyl and alkyl straight chains through the side chain, the spatial interaction between them and the main chain thiophene can change the stacking mode and the energy level of the molecules, thereby increasing the light conversion pathway and molecular solubility. This type of organic small molecule receptor material has excellent performance, excellent charge transfer characteristics and good intermolecular stacking, which helps to improve charge mobility and has better photovoltaic performance in the test of ternary organic solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Compound 1 prepared by the present invention 1 H NMR spectrum.
[0023] Figure 2 Compound 2 prepared by the present invention 1 H NMR spectrum.
[0024] Figure 3 Compound 3 prepared by the present invention 1 H NMR spectrum.
[0025] Figure 4 Compound 4 prepared by the present invention 1 H NMR spectrum.
[0026] Figure 5 Compound Y-C1 prepared by the present invention 1 H NMR spectrum.
[0027] Figure 6 Compound 5 prepared by the present invention 1 H NMR spectrum.
[0028] Figure 7 Compound 6 prepared by the present invention 1 H NMR spectrum.
[0029] Figure 8 Compound 7 prepared by the present invention 1 H NMR spectrum.
[0030] Figure 9 Compound 8 prepared by the present invention 1 H NMR spectrum.
[0031] Figure 10 Compound Y-C2 prepared by the present invention 1 H NMR spectrum.
[0032] Figure 11 This is the LC-MS spectrum of compound Y-C1 prepared in the present invention.
[0033] Figure 12 LC-MS spectrum of compound Y-C2 prepared in the present invention.
[0034] Figure 13 The current density-voltage (JV) test diagram of the binary organic solar device prepared in the present invention, (under a solar simulator (SAN-EI, XES-40S2-CE) of 100mW / cm 2 The current-voltage (JV) characteristics were measured using a Keithley 2450 source meter under an irradiation intensity of 1.5G AM.
[0035] Figure 14 This is a test chart of the external quantum efficiency (EQE) of the organic solar cell device prepared in the present invention (the EQE spectrum was analyzed using a certified Newport IPCE measurement system).
[0036] Figure 15 UV-visible spectra of compounds Y-C1 and Y-C2 in solution (S).
[0037] Figure 16 UV-visible spectrum test diagram of compounds Y-C1 and Y-C2 in film (F)
[0038] Figure 17 The electrochemical test results of compounds Y-C1, Y-C2 and PM6 are shown.
[0039] Figure 18 HOMO energy levels of compounds Y-C1, Y-C2 and PM6 and HOMO energy level result diagram. DETAILED DESCRIPTION
[0040] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0041] In the following examples, unless otherwise specified, the "water" used is deionized water.
[0042] In the following tests of the present invention, H NMR spectra were performed on an AVANCE NEO 400 MHz NMR spectrometer from Bruker, Germany. The solvent used was deuterated chloroform (CDCl 3 ) and the calibration was performed with tetramethylsilane (TMS).
[0043] Liquid chromatography was performed using a Shimadzu LCMS-2010EV liquid chromatography-mass spectrometer.
[0044] Example 1
[0045] The synthetic route of compound Y-C1 is as follows:
[0046]
[0047] (1) Synthesis of Compound 1:
[0048] At 0 ° C, oxalyl chloride (17.4 g, 137 mmol) was added to a solution of pentylcyclohexylcarboxylic acid (45.7 mmol) in dichloromethane (80 mL) and stirred at room temperature for 4 h. After removing the solvent and unreacted oxalyl chloride, the crude product was used directly in the next step. Anhydrous AlCl3 (45.7 mmol) was added in batches to a stirred mixture of 3-bromothiophene (45.7 mmol) and the prepared acid chloride (45.7 mmol). The resulting solution was stirred at room temperature for 3 h, and then cold water (200 mL) was slowly added to quench the reaction. The organic phase was extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. It was mixed with K2CO3 (50 mmol) and DMF (80 mL). Under a nitrogen atmosphere, ethyl mercaptoacetate (25 mmol) was added dropwise at 60 ° C, stirred overnight, and then poured into water ( 200mL), the organic phase was extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. Anhydrous ethanol (120mL) and NaOH (2.0g, 50mmol) were added, refluxed overnight, cooled to room temperature, acidified with concentrated hydrochloric acid, and the yellow solid was collected by filtration. The excess hydrochloric acid was washed with water and then washed with petroleum ether. After decantation, a mixture of the obtained light pink solid, copper powder (0.1mmol) and quinoline (60mL) was heated in a sand bath at 260°C and stirred at reflux for 4h. After the mixture was cooled to room temperature, n-hexane (200mL) was added to the quinoline mixture, and the mixture was washed with hydrochloric acid. The organic phase was extracted with petroleum ether, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. The mixture was purified by column chromatography (eluent: petroleum ether) to give 1 (8.3g, 46% yield in this step) as a colorless oily liquid. 1 HNMR see Figure 1.
[0049] (2) Synthesis of Compound 2:
[0050] Under nitrogen atmosphere, anhydrous tetrahydrofuran (120 mL) was added to compound 1 (21.5 mmol), and 2.4 M n-butyllithium (21.5 mmol) was added dropwise at 78°C. After stirring at -78°C for 1 h, tributyltin chloride (21.5 mmol) was added, and the mixture was gradually warmed to room temperature and stirred overnight. After the reaction, 100 mL of deionized water was added to quench, the organic phase was extracted with petroleum ether, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. Without further purification, it was added to a two-necked flask containing 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole (3.0 mmol), and a catalyst Pd(PPh3)Cl2 (0.18 mmol) was added. Anhydrous toluene (80 mL) was added under a nitrogen atmosphere and stirred at reflux for 12 h. After the reaction was completed, it was cooled to room temperature, the solvent was removed under reduced pressure, and purified by column chromatography (eluent: petroleum ether) to obtain a red solid 2 (1.61 g, yield of this step 56.7%). 1 H NMR see Figure 2 .
[0051] (3) Synthesis of compound 3:
[0052] A mixed solution of compound 2 (0.676 mmol), triethyl phosphite (5 mL), and o-dichlorobenzene (3.0 mL) was heated at 180 ° C under a nitrogen atmosphere to react overnight. After the reaction, o-dichlorobenzene was distilled off under reduced pressure to obtain a yellow solid for the next step. The obtained yellow solid was reacted with 1-bromo-2-ethylhexane (6.8 mmol), potassium carbonate (6.76 mmol), potassium iodide (0.27 mmol) and DMF (8.0 mL) at 80 ° C under a nitrogen atmosphere for 8 h. After the reaction was completed, water was added to quench the mixture, washed with saturated brine, and the organic phase was extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. Purification by column chromatography (eluent: petroleum ether) gave an orange solid 3 (310 mg, yield 42.3% in this step). 1 H NMR see Figure 3 .
[0053] (4) Synthesis of compound 4:
[0054] Under nitrogen atmosphere, phosphorus oxychloride (0.5 mL) was added to anhydrous DMF (3.0 mL) at 0°C and reacted for 0.5 h. Subsequently, a solution of compound 7 (0.144 mmol) in 1,2-dichloroethane (10 mL) was added to the mixed system and refluxed at 80°C overnight. After the reaction was completed, the mixture was quenched with saturated aqueous sodium carbonate solution and stirred for 1 h to fully hydrolyze the product. The organic phase was then extracted with dichloromethane and dried over anhydrous Na2SO4. After the solvent was removed under reduced pressure, it was purified by column chromatography (eluent: petroleum ether) to obtain an orange solid 4 (0.12 g, yield 72.6%). 1 H NMR see Figure 4 .
[0055] (5) Synthesis of Compound Y-C1:
[0056] To compound 4 (0.073 mmol) was added the terminal group 5,6-difluoro-3-(dicyanomethylene)indone (0.565 mmol), and under a nitrogen atmosphere, anhydrous chloroform and pyridine were added to the mixture, stirred and refluxed for 10 h. After the reaction was completed, the mixture was poured into methanol to dissolve the excess terminal reactant. The precipitate was filtered and purified by silica gel chromatography to obtain a black purple solid Y-C1 (90 mg, yield of 74% in this step). 1 H NMR see Figure 5 .
[0057] Example 2
[0058] The synthetic route of compound Y-C2 is as follows: the steps and products are the same as those in Example 1, except that the concentrations of the reactants and the yields of each step are slightly different.
[0059]
[0060] (6) Synthesis of Compound 5:
[0061] At 0 ° C, oxalyl chloride (151 mmol) was added to a solution of pentylcyclohexylcarboxylic acid (50.3 mmol) in dichloromethane (120 mL), stirred at room temperature for 4 h, and after removing the solvent and the remaining oxalyl chloride, the crude product was used directly in the next step. Anhydrous AlCl3 (50.3 mmol) was added in batches to a stirred mixture of 3-bromothiophene (50.3 mmol) and the prepared acid chloride (50.3 mmol). The resulting solution was stirred at room temperature for 4 h, and then cold water (200 mL) was slowly added to quench the reaction. The organic phase was extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. It was mixed with K2CO3 (50 mmol) and DMF (80 mL). Under a nitrogen atmosphere, ethyl mercaptoacetate (27.5 mmol) was added dropwise at 60 ° C, stirred overnight, and then poured into water (200 mL). The organic phase was extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. Anhydrous ethanol was added. (120 mL) and NaOH (55.0 mmol), reflux overnight, cool to room temperature, acidify the liquid with concentrated hydrochloric acid, collect the yellow solid by filtration, wash the excess hydrochloric acid with water, and then wash with petroleum ether and decant. A mixture of the obtained light pink solid, copper powder (0.11 mmol) and quinoline (60 mL) is heated in a sand bath at 260°C, stirred and refluxed for 4 h, and the mixture is cooled to room temperature. Hexane (200 mL) is added to the quinoline mixture, and the mixture is washed with hydrochloric acid. The organic phase is extracted with petroleum ether, dried over anhydrous Na2SO4, and the solvent is removed under reduced pressure. Purification by column chromatography (eluent: petroleum ether) gives 5 as a colorless oily liquid (8.9 g, 42% yield in this step). 1 HNMR see Figure 6 .
[0062] (7) Synthesis of Compound 6:
[0063] Under nitrogen atmosphere, anhydrous tetrahydrofuran (120 mL) was added to compound 5 (24.7 mmol), and 2.4 M n-butyl lithium (24.7 mmol) was added dropwise at 78 ° C. After stirring at -78 ° C for 1 h, tributyltin chloride (24.7 mmol) was added, and then the temperature was gradually raised to room temperature and stirred overnight. After the reaction was completed, 100 mL of deionized water was added to quench the reaction, and the organic phase was extracted with petroleum ether and anhydrous N a2 After drying over SO4 and removing the solvent under reduced pressure, the mixture was added to a two-necked flask containing 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole (3.5 mmol) without further purification, and catalyst Pd(PPh3)Cl2 (0.21 mmol) was added. Anhydrous toluene (80 mL) was added under nitrogen atmosphere, and the mixture was stirred and refluxed for 12 h. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed under reduced pressure. The mixture was purified by column chromatography (eluent: petroleum ether) to obtain a red solid 6 (1.87 g, yield of this step 58.7%).1 H NMR see Figure 7 .
[0064] (8) Synthesis of Compound 7:
[0065] A mixed solution of compound 6 (0.676 mmol), triethyl phosphite (5 mL), and o-dichlorobenzene (3.0 mL) was heated at 180°C under a nitrogen atmosphere to react overnight. After the reaction was completed, o-dichlorobenzene was distilled off under reduced pressure to obtain a yellow solid for the next step. The obtained yellow solid, 1-bromo-2-ethylhexane (6.8 mmol), potassium carbonate (6.76 mmol), potassium iodide (0.27 mmol) and DMF (8.0 mL) were reacted at 80°C for 8 h under a nitrogen atmosphere. After the reaction was completed, water was added to quench the mixture, the organic phase was washed with saturated brine and extracted with dichloromethane, dried over anhydrous Na2SO4, the solvent was removed under reduced pressure, and purified by column chromatography (eluent: petroleum ether) to obtain an orange solid 7 (300 mg, yield of 41.5% in this step). 1 H NMR see Figure 8 .
[0066] (9) Synthesis of Compound 8:
[0067] Under nitrogen atmosphere, phosphorus oxychloride (0.5 mL) was added to anhydrous DMF (3.0 mL) at 0°C and reacted for 0.5 h. Subsequently, a solution of compound 7 (0.161 mmol) in 1,2-dichloroethane (10 mL) was added to the mixture and refluxed at 80°C overnight. After the reaction was completed, the mixture was quenched with saturated aqueous sodium carbonate solution and stirred for 1 h to fully hydrolyze the product. The organic phase was then extracted with dichloromethane, dried over anhydrous Na2SO4, and the solvent was removed under reduced pressure. After purification by column chromatography (eluent: petroleum ether), an orange solid 8 (0.14 g, yield 74.6%) was obtained. 1 H NMR see Figure 9 .
[0068] (10) Synthesis of Compound Y-C2:
[0069] To compound 8 (0.088 mmol) was added the terminal group 5,6-difluoro-3-(dicyanomethylene)indone (0.678 mmol). Under a nitrogen atmosphere, anhydrous chloroform and pyridine were added to the mixture, stirred and refluxed for 10 hours. After the reaction, the mixture was poured into methanol to dissolve the excess terminal reactant. The precipitate was filtered and purified by silica gel chromatography to obtain a dark purple solid Y-C2 (100 mg, yield 75% in this step). 1 H NMR see Figure 10 .
[0070] Example 3: Organic solar cell device characterization
[0071] Preparation of organic photovoltaic devices:
[0072] (1) After ultrasonic cleaning, ITO glass (indium tin oxide conductive glass) was treated with oxygen-plasma. PEDOT:PSS poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (from Xi'an Yuri Solar Energy Technology Co., Ltd., PEDOT:PSS AI4083, product number: 306020, a mixed solution prepared at the time of purchase) was spin-coated on the ITO at 5000 rpm and annealed at 150°C for 15 minutes to obtain a substrate with a surface film thickness of about 40 nm.
[0073] (2) Then, the small molecule compounds Y-C1 and Y-C2 prepared in Examples 1 and 2 were respectively used as acceptor materials and mixed with the donor PM6 (structural formula shown below) to form a binary organic solar device (the mass ratio of the donor and acceptor materials was preferably 1:1.2). A mixed solvent of diiodomethane and chloroform (the volume ratio of diiodomethane to chloroform was 0.3 μL:100 μL) was added to prepare a blend solution (the total concentration of the donor and the acceptor was 16 mg / mL), and the blend solution was coated on the substrate in step (1) at a spin coating speed of 3000 rpm, and an active layer with a thickness of about 120 nm was coated on the surface of the substrate.
[0074] (3) The substrate obtained in step (2) was placed in a 60 nm culture dish and thermally annealed (85°C, 5 min). Next, a 10 nm thick thin film of an electron transport layer (PDINN) (structural formula shown below) was applied to the active layer using a spin coating speed of 3500 rpm. Finally, a 100 nm thick silver layer was deposited on top of the electron transport layer by evaporation.
[0075]
[0076] The specific solar cell efficiency is shown in Table 1 (the equipment used in the laboratory of the present invention is a solar simulator, which is calibrated with a silicon solar cell. All tests are measured under 1 simulated sunlight, 100mW / cm 2 ).
[0077] Table 1 Photovoltaic device photoelectric conversion efficiency
[0078] Active layer <![CDATA[V 0C (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE (%) PM6:Y6 (1:1.2) 0.847 26.5 74.3 16.7 PM6:Y-C1(1:1.2) 0.862 26.3 76.7 17.4 PM6:Y-C2(1:1.2) 0.897 26.8 79.4 19.1
[0079] As shown in Table 1, the binary organic solar cell devices prepared using compounds Y-C1 and Y-C2 as acceptors exhibit significantly higher efficiencies than conventional PM6:Y6 devices. This class of small molecules possesses a unique and well-defined molecular structure in organic solar cells, resulting in minimal variability between batches of materials and devices. Therefore, they offer distinct advantages in the commercialization of organic solar cells.
[0080] Compound Y-C1 and compound Y-C2 prepared in the present invention were mixed as acceptor materials with donor PM6 to form a binary organic solar device, and then the JV curve was measured under one simulated sunlight, as shown in FIG. Figure 13 As shown. Figure 13 It can be seen that the efficiency of the binary devices of compound Y-C1 and compound Y-C2 prepared by the present invention is significantly higher than that of the PM6:Y6 binary device.
[0081] By using the integrated system to measure high sensitivity EQE, the test graph obtained is as follows Figure 14 As shown, the photocurrent is amplified and modulated by a lock-in instrument. This test proves that the EQE spectrum of the PM6:Y-C1 binary device is better than that of the PM6:Y-C2 binary device compared to the integrated J of the solar spectrum (AM 1.5G). sc The values are consistent with those obtained from the JV curves with an error of less than 5%, which means that Y-C1 and Y-C2 have more efficient internal charge transfer and more absorbed photons generate charge carriers.
[0082] from Figure 15-16 As can be seen in the figure, the absorption spectra of compounds Y-C1 and Y-C2 in solution are almost identical. Compared with Y-C2, Y-C1 in the film has a broader absorption spectrum, which indicates that the small molecules with greater steric hindrance have good intermolecular stacking, which helps to improve charge mobility.
[0083] Figure 17 Electrochemical test results: Cyclic voltammetry (CV) measurements were performed on a CHI660D electrochemical workstation using a three-electrode system (glassy carbon electrode as working electrode, Ag / Ag+ electrode as reference electrode, and platinum wire counter electrode). A nitrogen-saturated solution of 0.1 mol / L tetrabutylammonium hexafluorophosphate in acetonitrile was used as the electrolyte. Ferrocene-ferrocene salt (Fc / Fc+) was used as the internal standard, and the absolute energy relative to vacuum was -4.8 eV. The HOMO and LUMO energy levels of the material were determined according to the equation:
[0084] EHOMO / LUMO=-(E ox / E red -E Fc / Fc+ +4.80).
[0085] from Figure 18 It can be calculated that the HOMO energy level of compound Y-C1 is -5.67eV, and its LUMO energy level is -4.03eV. The HOMO energy level of compound Y-C2 is -5.65eV, and its LUMO energy level is -4.00eV, which is conducive to exciton dissociation and improves the photoelectric conversion efficiency of photovoltaic devices.
[0086] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.
Claims
1. An acceptor material containing a cyclohexyl side chain, characterized in that: Its structural formula is one of Y-C1 or Y-C2, as shown below:
2. A method for preparing an acceptor material containing a cyclohexyl side chain, characterized in that: The following steps are involved: Step 1: Using trans-p-pentylcyclohexylcarboxylic acid as a raw material, first react with tribromothiophene through Friedel-Crafts acylation, and then use ethyl thioglycolate for cyclization and hydrolysis to obtain 3-alkyl-thieno[3,2-b]thiophene-2-carboxylic acid; and then perform high-temperature decarboxylation reaction under the catalysis of copper powder to obtain compound A; Step 2: Compound B is obtained by Stille coupling reaction catalyzed by Pd(PPh3)2Cl2; Step 3: Compound B undergoes intramolecular Cadogan cyclization reaction with triethyl phosphite, and then undergoes alkylation reaction with 2-ethylhexyl as a side chain to obtain compound C; Step 4: Compound C is subjected to Vilsmeier Haack reaction to obtain dialdehyde compound D; Step 5: Compound D and terminal unit IC-2F are subjected to Knoevenagel polycondensation reaction to obtain compound E, ie, a receptor material containing a cyclohexyl side chain.
3. The acceptor material containing cyclohexyl side chains and its preparation method and application according to claim 2, characterized in that: The specific operation of step 1 is as follows: at 0°C, oxalyl chloride is added to a dichloromethane solution of the compound trans-p-pentylcyclohexylcarboxylic acid, stirred at room temperature for 5 hours, and after removing the solvent and the remaining oxalyl chloride, a colorless acid chloride is obtained; then, anhydrous AlCl3 is added in batches to a stirred solution of halogenated thiophene and the prepared acid chloride, the obtained solution is stirred at room temperature for 4 hours, and then cold water is slowly added to quench the reaction, the organic phase is extracted with dichloromethane, dried with anhydrous Na2SO4, and the solvent is removed under reduced pressure to obtain an orange oily liquid, the oily liquid and K2CO3 are mixed in a DMF solvent, ethyl thioglycolate is added dropwise at 60°C in a nitrogen atmosphere, stirred overnight, and then poured into water, the organic phase is extracted with dichloromethane, dried with anhydrous Na2SO4, and NaOH is added after the solvent is removed under reduced pressure, refluxed in an ethanol solvent overnight, cooled to room temperature, acidified with concentrated hydrochloric acid, and a yellow solid is collected by filtration. Excess hydrochloric acid is washed with water and then with petroleum ether to obtain a light pink solid, which is then mixed with copper powder and heated in a sand bath at 260° C. in a quinoline solvent, stirred and refluxed for 3 hours, and the mixture is cooled to room temperature, n-hexane is added to the mixture, and then the mixture is washed with hydrochloric acid, and then the organic phase is extracted with petroleum ether, dried over anhydrous Na2SO4, and the solvent is removed under reduced pressure. The compound A is purified by silica gel chromatography to obtain a colorless oily liquid compound A; in the above operation, the molar ratio of trans-p-pentylcyclohexylcarboxylic acid to the oxalyl chloride is (1-1.2):3, preferably 1:3; the molar ratio of the 3-bromothiophene to the acyl chloride is 1:1; the molar ratio of the 3-bromothiophene to anhydrous AlCl3 is 1:1; the molar ratio of the 3-bromothiophene to K2CO3 is 1:2; the molar ratio of the 3-bromothiophene to ethyl thioglycolate is 1:1; and the molar ratio of the 3-bromothiophene to NaOH is 1:
2.
4. The acceptor material containing cyclohexyl side chains and its preparation method and use according to claim 2, characterized in that: The step 2 is specifically as follows: under a nitrogen atmosphere, anhydrous tetrahydrofuran is used as a solvent, compound A is used as a raw material, 2.4M n-butyl lithium is added dropwise at -78°C, after stirring at -78°C for 1 hour, tributyltin chloride is added, then the temperature is gradually raised to room temperature, stirred overnight, after the reaction is completed, deionized water is added to quench, the organic phase is extracted with petroleum ether, dried with anhydrous Na2SO4, the solvent is removed under reduced pressure, anhydrous toluene solution is added, and then 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole and catalyst Pd(PPh3)Cl2 are added, stirred and refluxed for 12 hours, after the reaction is completed, it is cooled to room temperature, the solvent is removed under reduced pressure, and a red solid compound B is obtained by purification on a silica gel chromatography column; in the above operation, the molar ratio of compound A to n-butyl lithium is 1:1; the molar ratio of compound A to tributyltin chloride is 1:
1. The molar ratio of the compound A to 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole is 3:
1.
5. The acceptor material containing cyclohexyl side chains and its preparation method and use according to claim 2, characterized in that: The step 3 is specifically as follows: in a nitrogen atmosphere, a mixed solvent of triethyl phosphite and o-dichlorobenzene of compound B is heated at 180° C. to react overnight. After the reaction is completed, the solvent is removed by distillation under reduced pressure to obtain a yellow solid for the next step. 1-bromo-2-ethylhexane, potassium carbonate, potassium iodide and DMF are added to the obtained yellow solid, and the mixture is reacted at 80° C. for 12 hours in a nitrogen atmosphere. After the reaction is completed, water is added to quench the mixture, the mixture is washed with saturated brine, and the organic phase is extracted with dichloromethane, dried over anhydrous Na2SO4, the solvent is removed under reduced pressure, and the mixture is purified by a silica gel chromatography column to obtain an orange solid compound C. In the above operation, the molar ratio of compound B to 1-bromo-2-ethylhexane is 1:10; the molar ratio of compound B to potassium carbonate is 1:10; and the molar ratio of compound B to potassium iodide is 3:
1.
6. The acceptor material containing cyclohexyl side chains and its preparation method and use according to claim 2, characterized in that: The step 4 is specifically as follows: under a nitrogen atmosphere, adding phosphorus oxychloride to anhydrous DMF at 0°C, reacting for 0.5h, then adding a solution of compound C in 1,2-dichloroethane to the mixed system, reflux at 80°C for overnight reaction, quenching with a saturated aqueous sodium carbonate solution after the reaction is completed, and stirring for 1h to fully hydrolyze the product, then extracting the organic phase with dichloromethane, drying with anhydrous Na2SO4, removing the solvent under reduced pressure, and purifying with a silica gel chromatography column to obtain an orange solid compound D; wherein the molar ratio of compound C to phosphorus oxychloride is 1:
3.
7. The acceptor material containing cyclohexyl side chains and its preparation method and use according to claim 2, characterized in that: The step 5 is specifically as follows: adding terminal group 5,6-difluoro-3-(dicyanomethylidene)indone to compound D, adding anhydrous chloroform and pyridine to the mixed system under nitrogen atmosphere, stirring and refluxing for 12 hours, after the reaction is completed, pouring the mixed system into methanol to dissolve excess terminal reactant, filtering the precipitate and purifying it with a silica gel chromatography column to obtain a black purple solid compound E; wherein the ratio of compound D to 5,6-difluoro-3-(dicyanomethylidene)indone is 1:
7.
8. Use of the acceptor material containing cyclohexyl side chains according to claim 1 or the acceptor material containing cyclohexyl side chains obtained by the preparation method according to claims 2 to 7 in the preparation of an organic solar cell device.
9. The use according to claim 8, characterized in that: The donor material selected in the preparation of the organic solar cell device is PM6; the mass ratio of the PM6 to the small molecule acceptor material containing cyclohexyl side chains is 1:1.2.
Citation Information
Patent Citations
Dithiophene and dithienobenzothiadiazole conjugated polymer with alkyl chain and cycloheptyl at same time as well as preparation method and application of dithiophene and dithienobenzothiadiazole conjugated polymer
CN118184969A
Cited By
Compound formed by coupling asymmetric Y-series receptor and fluorene as well as preparation method and application of compound
CN121609712A
A compound of asymmetric y series acceptor and fluorene coupling and its preparation method and application
CN121609712B
A class of receptor materials with locking side chains, their preparation methods and applications
CN122772006A